Computer-assisted cognitive rehabilitation in neurological patients: state-of-art and future perspectives - Maggio, Maria Grazia; De Bartolo, Daniela; Calabrò, Rocco Salvatore; Ciancarelli, Irene; Cerasa, Antonio; Tonin, Paolo; Di Iulio, Fulvia; Paolucci, Stefano; Antonucci, Gabriella; Morone, Giovanni; Iosa, Marco (Frontiers in Neurology, 2023)
Background and aim Advances in computing technology enabled researchers and clinicians to exploit technological devices for cognitive training and rehabilitation interventions. This expert review aims to describe the available software and device used for cognitive training or rehabilitation interventions of patients with neurological disorders. Methods A scoping review was carried out to analyze commercial devices/software for computerized cognitive training (CCT) in terms of feasibility and efficacy in both clinical and home settings. Several cognitive domains responding to the different patients’ needs are covered. Results This review showed that cognitive training for patients with neurological diseases is largely covered by several devices that are widely used and validated in the hospital setting but with few translations to remote/home applications. It has been demonstrated that technology and software-based devices are potential and valuable tools to administer remotely cognitive rehabilitation with accessible costs. Conclusion According to our results, CCT entails the possibility to continue cognitive training also in different settings, such as home, which is a significant breakthrough for the improvement of community care. Other possible areas of use should be the increase in the amount of cognitive therapy in the free time during the hospital stay.